Analisis Normatif Surah al-Isrā’ Ayat 32 terhadap Perilaku Seksual Pranikah Remaja: Studi Kasus di Desa Siunggam, Kabupaten Padang Lawas Utara - Abdul Habib Harahap (Yayasan Albahriah Jamiah Indonesia, 2026)
The increasing phenomenon of premarital sexual behavior among adolescents in rural areas indicates a shift in previously relatively strong patterns of social relations and normative control, including in Siunggam Village, North Padang Lawas Regency. This has given rise to tension between social practices and Quranic norms, particularly the content of Surah al-Isra’ verse 32, which prohibits approaching adultery. This study aims to analyze the normative construction of this verse and examine its relevance to the reality of adolescent premarital sexual behavior in a rural social context. The approach used is normative-empirical, with a qualitative research design; normative data are obtained through analysis of classical and contemporary interpretations, while empirical data are collected through in-depth interviews, field observations, and documentation, and then analyzed using thematic and interpretative-contextual analysis techniques. The results of the study indicate that the phrase prohibiting “approaching adultery” contains a preventive construction that is gradual and protective, encompassing restrictions on all socio-psychological prerequisites that could potentially lead to sexual relations outside of marriage. At the practical level, it was found that digital interaction, weak family supervision, and the normalization of promiscuity are dominant factors that reduce the binding power of religious norms. The level of congruence between textual norms and social practices ranges from low to moderate, characterized by the symbolic internalization of norms, with inconsistent enactment in behavior. Conceptually, this study contributes to strengthening the normative-contextual interpretation model that integrates textual analysis and social dynamics as a basis for developing Islamic social studies.